Comparative Study of Algorithms for the Conversion From Surface Mesh Models to Volume Mesh Models - Youxi Wang; Qi Pang; Meng Li; Yang Liu (Advances in Civil Engineering)
The study delves into the performance of different algorithms in the process of converting surface mesh models (SMMs) into volume mesh models (VMMs) required for finite element analysis. The experiment compared the Initial mesh, Delaunay, Frontal, and HXT algorithms, analyzing their central processing unit (CPU) runtime, node count, element count, and model size when processing simple models under default control parameters. The results showed that the Frontal algorithm performed the best in the conversion of simple models with a CPU runtime of 0.001 s, while the Delaunay algorithm took relatively longer. For complex models, the Initial mesh, Delaunay, and Frontal algorithms were all successful in completing the conversion, but the HXT algorithm failed, highlighting the importance of algorithm selection. The Delaunay algorithm performed best in terms of efficiency and model size, while the Frontal algorithm had an advantage in model refinement. Although the Initial mesh algorithm had a more balanced number of nodes and elements, its longer CPU runtime indicates potential for efficiency improvement. In addition, the randomness of the HXT algorithm in mesh generation led to variations in results, which requires further optimization to improve the consistency and robustness of the algorithm. Future research will focus on algorithm optimization, particularly enhancing the HXT algorithm’s ability to handle complex models, developing automated parameter selection mechanisms, exploring the application of algorithms in other engineering fields, and achieving better integration of algorithms with computer-aided design (CAD)/computer-aided engineering (CAE) workflows.